PERENCANAAN PEMBANGUNAN PARTISIPATIF DI DESA KETONG KECAMATAN BALAESANG TANJUNG KABUPATEN DONGGALA - Andriyana, Andriyana (Katalogis, 2015)
This research aims at finding out the planning of people participation development in Ketong village, Balaesang Tanjung District, Donggala Regency. The researcher quotes Stonersâ€™ idea (1992: 202) that planning steps cover: 1) setting goals; 2) determining the present situation; 3) identifying opportunities and threats of the goals. This is a qualitative research. This research result shows that from the aspect of goals setting, the goals of Musrenbang have been implemented according to the guidance of Musrenbang implementation. From the second aspect, organizations of Ketong village have less involvement. The third aspect shows that Musrenbang in the level of village has been implemented as it should be, but there were two constraints in the process, they were the lack of cooperation of stakeholders and the lack of funds in holding Musrenbang. Finally, it is concluded thatÂ Â the planning of people participation development in Ketong village is categorized as non optimal, so that there must be improvement in the planning process.